Communisms and the Cold War, 1944-1986. - Communist Party of Great Britain; Archive Trust of the Communist Party of Great Britain (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2020)
This collection contains reports and other records compiled by the Communist Party of Great Britain's (CPGB) International Department between 1944 and 1986—a period which begins immediately after the dissolution of the Communist International (Comintern) and ends shortly before the collapse of the Soviet Union.
Date range: 1944-1986.
Keywords: Communism -- History -- 20th century -- Sources; Communism -- Soviet Union -- History -- 20th century -- Sources; Communism -- China -- History -- 20th century -- Sources